Correlações genéticas e capacidade geral de combinação em linhagens endogâmicas de milho (Zea mays L.) - Torres Vianna, Ronaldo; Silva, José Carlos (Revista Ceres, 2025)
The general combining ability of inbred lines of maize belonging to the Fede- ral University of Vicosa (Viçosa, Minas Gerais, Brazil) was studied by evaluation of half-sib progenies resulting from the topcross between flint inbred lines x Dent Composite B (Experiment 1) and dent inbred lines x Flint Composite B (Experi- ment 2).